FUNCTIONAL AND FORMAL APPROACHES TO THE INTERPRETATION OF THE SUBPHONEMIC LEVEL UNITS IN STRUCTURAL LINGUISTICS - Vasko, Roman (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the analysis of the contribution to the phonological theory made by four schools of structural linguistics: (i) the Prague linguistic circle, the most important achievement of which was the creation by N. S. Trubetzkoy of a detailed and holistic teaching about the sound structure of language (phonology); (ii) the French school of functional linguistics, whose representative A. Martinet developed principles of diachronic phonology and procedure for identifying phonemes, between which a certain phonetic distance is necessary; (iii) The American linguistic school of L. Bloomfield and E. Sapir, from which two branches of American linguistics originate - descriptivism, the most important theoretical discovery of which was the doctrine of the hierarchy of language structure – from lower levels to higher ones, and generative linguistics by N. Chomsky and his followers, who, retaining the idea of hierarchy, changed its vector to the opposite – speech is generated from higher to lower levels; (іv) the Copenhagen glossematics, which defined the phoneme as a unit of the expression plane, which as an element of pure relations is manifested in sounds, but does not in itself contain anything physical, and for identification and delimitation of linguistic units commutation test is used. The activity of these four schools of structural linguistics has completed the creation of phonology. _____________ References Blumfil’d, L. Jazyk (Moskva, Progress, 1968), 606. Vinogradov, V. A. «Ozperand [as΄p΄iránt]. K probleme giperfonemy.» Fonetika. Fonologija. Grammatika. K semidesjatiletiju A. A. Reformatskogo (1971): 96-105. El’mslev, L. «Prolegomeny k teorii jazyka.» Novoe v lingvistike 1 (1960): 264-389. Zhirmunskij, V. M. Istorija nemeckogo jazyka, 5-oe izd., peresmotr. i ispravl (Moskva, Vysshaja shkola, 1965), 408. Ivanov, Val. Vas. Istoricheskaja fonologija russkogo jazyka (Moskva, Prosveshhenie, 1968), 354. Knjazev, S. V. «O nekotoryh fonologicheskih edinicah v russkom jazyke.» Mezhdunarodnyj kongress «Russkij jazyk: istoricheskie sud’by i sovremennost’» (g. Moskva, 13 – 16 marta 2001 g., Sekcija “Fonetika i fonologija russkogo jazyka”): 236-237. Krupatkin, Ja. B. «K istoriko-fonologicheskim rekonstrukcijam (Kombinatornye varianty i prichinnost’).» Іnozemna fіlologіja 3 (1965): 7-12. Kuz’menko, Ju. K. «Faktory fonologicheskoj jevoljucii skandinavskih jazykov.» Avtoref. dis. d-ra. filol. nauk, Leningrad, 1984. Levi-Stross, K. Strukturnaja antropologija, perevod s franc. pod red. i s prim. Vjach. Vs. Ivanova (Moskva, JeKSMO-Press, 2001), 512. Martine, A. Princip jekonomii v foneticheskih izmenenijah. Problemy diahronicheskoj fonologii, perevod s franc. pod red. i so vstup. st. V. A. Zveginceva (Moskva, Izd-vo inostrannoj lit-ry, 1960), 262. Martine, A. Osnovy obshhej lingvistiki, perevod s franc. V. V. Shevoroshkina, pod red. i so vstup. st. V. A. Zveginceva, 2-e izd. (Moskva, Jeditorial URSS, 2004), 224. Meje, A. Osnovnye osobennosti germanskoj gruppy jazykov, perevod s 5-go franc. izd. (Moskva, Izd-vo inostr. lit-ry, 1952), 168. Panov, M. V. Russkaja fonetika (Moskva, Prosveshhenie, 1967), 438. Plotkin, V. Ja. Dinamika anglijskoj fonologicheskoj sistemy (Novosibirsk, Zap.-Sib. knizhnoe izd-vo, 1967), 169. Plotkin, V. Ja. «O pervichnoj fonologicheskoj edinice.» Grammaticheskie i foneticheskie issledovanija po germanskim jazykam (1977): 138-168. Sidorov, V. N. «O Moskovskoj fonologicheskoj shkole.» Razvitie fonetiki sovremennogo russkogo jazyka: fonologicheskie podsistemy (1971): 7-19. Solncev, V. M. Jazyk kak sistemno-strukturnoe obrazovanie (Moskva, Nauka, 1977), 342. Sravnitel’naja grammatika germanskih jazykov [v 4-h t.] (Moskva, Izd-vo AN SSSR). T. I (1962), 204; T. II (1962), 402; T. III (1963), 456; T. IV (1966), 496. Steblin-Kamenskij, M. I. «Sushhnost’ germanskih peredvizhenij soglasnyh.» Vestnik LGU, vyp.4, № 20 (1961): 102-108. Sjepir, Je. «Jazyk.» Izbrannye trudy po jazykoznaniju i kul’turologii (2002): 223-247. Trubeckoj, N. S. Osnovy fonologii (Moskva, Izd-vo inostrannoj lit-ry, 1960), 372. Shaumjan, S.K. Problemy teoreticheskoj fonologii (Moskva, AN SSSR, 1962), 194. Shherba,L. V. «O trojakom aspekte jazykovyh javlenij i ob єksperimente v jazykoznanii.» Jazykovaja sistema i rechevaja dejatel’nost’, avt. Shherba L. V., pod red. L. R. Zindera i M. I. Matusevich, 2-e izd. stereotipnoe (Moskva, Jeditorial URSS, 2004): 24-39. Akamatsu, T. Essentials of Functional Phonology (Louvain-La-Neuve, Peeters, 1992), 191. Alonso, A. «Notas de fonemática.» Estudios lingüísticos: temas españoles (Madrid, Gredos, 1982): 237-259. Basbøll, H. The Phonology of Danish (New York, Oxford University Press, 2005), 596. Benediktsson, H. «The Proto-Germanic Vowel System.» To honour Roman Jakobson: Essays on the occasion of his birthday 1 (The Hague – Paris, Mouton, 1967): 174-196. Bloch, B. «A Set of Postulates for Phonemic Analysis.» Language24, № 1 (1948): 3-46. Bloomfield, L. «A Set of Postulates for the Science of Language.» Language 2 (1926): 153-164. Bloomfield, L. Language (New York, Holt, Rinehart & Winston, 1933), 564. Fischer-Jørgensen, E. The Commutation Test and Its Application to Phonemic Analysis (Indianapolis, Bobbs-Merrill, 1956), 12. Fischer-Jørgensen, E. Trends in Phonological Theory. A Historical Introduction. Travaux du Cercle Linguistique de Copenhagen, XXVII (Copenhagen, C. A. Reitzel, 1995), 475. Greenberg, J. H. «Synchronic and Diachronic Universals in Phonology.» Language, 42, № 2 (1966): 508-517. Harris, Z. S. Methods in Structural Linguistics (Chicago, University of Chicago Press, 1951), 384. Harris, Z. S. Spanish Phonology (Cambridge, MA: M.I.T Press, 1969), [xiii] + 218. Haugen, E. The Scandinavian Languages. An Introduction to their History (Cambridge, MA, Harvard University Press, 1976), 507. Haugen, E. Scandinavian Language Structures. A Comparative Historical Survey (Tűbingen, Max Niemeyer Verlag, 1982), 225. Hjelmslev, «Omkring sprogteoriens grundlæggelse.» Festskrift udgivet af Københavns Universitet i anledning af Universitetets aarfest, November, 1943 (København, Akademisk Forlag, 1943): 3-113. Hjelmslev, L. «La stratification du langage.» Word, Vol.10 (1954): 163-188. Hjelmslev, L. a) Ensayos lingüísticos (Madrid, Gredos, 1972), 358. Hjelmslev, L. b)Sprogsystem og Sprogforandring (København: Naturmetodens Sproginstitut; Nordisk Sprog–og–Kulturforlag, 1972), Hockett, Ch.F. «A System of Descriptive Phonology.» Language, Vol. 18 (1965): 3-21. Hockett, Ch. F. A Manual of Phonology. Indiana University Publications in Anthropology and Linguistics. Memoir II (Baltimore, MD., Waverly Press; Indiana University Press, 1955), Hockett, Ch. F. «Linguistic Elements and Their Relations.» Language, 37, № 1 (1961): 29-53. Hockett, Ch. F. «Sound Change.» Language,41, № 2 (1965): 185-204. Hockett, Ch. F. Language, Mathematics and Linguistics (The Hague, Mouton, 1967), 243. Hockett, Ch. F. «Two Fundamental Problems in Phonemics.» Phonological Theory: Evolution and Current Practice, ed. V. B. Makkai (New York, Holt, Reinhart and Winston, Inc., 1972): 200-210. Hogg, R. M. «Phonology and Morphology.» The Cambridge History of the English language. Vol. I. The Beginnings to 1066. General ed. R. M. Hogg (Cambridge, Cambridge University Press, 1994): 67-167. Jakobson, R. «Kindersprache, Aphasie und allgemeine Lautgesetze.» Selected Writings, Vol. 1: Phonological Studies, 2nd expanded ed. (The Hague; Paris, Mouton, 1971): 328-401. Jakobson, R. «Principes de Phonologie Historique.» Selected Writings, Vol. 1: Phonological Studies, 2nd expanded ed. (The Hague; Paris, Mouton, 1971): 202-220. Jakobson, R. «Remarques sur l’évolution phonologique du russe comparée à celle des autres langues slaves.» Selected Writings, Vol. 1: Phonological Studies, 2nd expanded ed. (The Hague; Paris, Mouton, 1971): 7-116. Jakobson, R., Waugh, L. The Sound Shape of Language. Assisted by Martha Taytor, 2nd (Berlin; New York; Amsterdam, Mouton de Gruyter, 1987), 335. Jones, D. An Outline of English Phonetics, 9th (Cambridge, Heffer, 1972), 376. Kristoffersen, The Phonology of Norwegian (Oxford, Oxford University Press, 2000), 366. Lehmann, W. P. Language: An Introduction (New York, Random House, 1983), 241. Lévi-Strauss, Structural Anthropology in 2 vol., (New York, Basic Books, 1976): Vol.I, 398 p.; Vol. II, 372. Martinet, A. Phonology as Functional Phonetics (London, Geoffrey Cumberlege; Oxford University Press, 1950), 40. Martinet, A. «Substance phonique et traits distinctifs.» Bulletin de la Société de Linguistique de Paris, № 53 (1958): 72-85. Martinet, A. Évolution des Langues et Reconstruction (Paris, Presses Universitaires de France, 1975), 264. Nida, E. A. Componential Analysis of Meaning: An Introduction to Semantic Structures (The Hague, Mouton, 1975), 272. The Nordic Languages: An International Handbook of the History of the North Germanic Languages,I, II, ed. by O. Bandle et al. (Berlin; New York: Walter de Gruyter): Vol. I (2002): 1-1057; Vol. II (2005): 1058-2208. de Saussure F. Course in General Linguistics (New York; Toronto; London, McGraw-Hill Book Company, 1959), 240. Skautrup, P. Det danske sprogs historie. Nærværende 2 oplag (1968) (København, Gyldendalske boghandel Nordisk Forlag):I: Fra guldhornene til Jyske Lov, 352; Bd. II: Fra unionsbrevet til Danske Lov, 455; Bd. III: Fra Holbergs komedier til H. C. Andersens eventyr, 481; Bd. IV: Fra J. P. Jacobsen til Johs. V. Jensen, 342; Bd. V: Register (1970), 360. Swadesh, M. La lingüística como instrumento de la historia (Mexico, Instituto Nacional de Antropología e Historia, 1960), 35. Trager, G. L. Language and Languages (San-Francisco: Chandler Pub. Co., 1972), 378. Trnka, B. «From Germanic to English. A Chapter from the Historical English Phonology.» Recueil Linguistique de Bratislava, №1 (1948): 139-149. Twaddell, W. F. «On Defining the Phoneme.» Readings in Linguistics (Chicago; London, The University of Chicago Press, 1958): 55-80. Vachek, J. «Phonemes and Phonological Units.» Travaux du Cercle Linguistique de Prague VI (Prague, 1936): 235- Reprinted in A Prague School Reader in Linguistics compiled by J. Vachek, 1st ed. (Bloomington, Indiana University Press, 1964): 143-149. Vennemann, Th. «The Phonology of Gothic Vowels.» Language, Vol. 47, № 1 (1971): 90-132. List of lexicographical sources Althochdeutsches Wörterbuch. Analyse der Wortfamilienstrukturen des Althochdeutschen, zugleich Grundlegung einer zukünftigen Strukturgeschichte des deutschen Wortschatzes von Jochen Splett (Berlin; New York, Walter de Gruyter, 1993): Band I,1:Einleitung; Wortfamilien A – L, 578; Band I,2: Wortfamilien M – Z, 662; Band II: Präfixwörter; Suffixwörter; Alphabetischer Index, Altnordisches etymologisches Wörterbuch von Jan de Vries, Zweite verbesserte Auflage (Leiden; Boston; Köln, Brill, 2000), An Anglo-Saxon Dictionary. Based on the Manuscript Collections of Joseph Bosworth, edited and enlarged by T. Northcote Toller (1997), 1302, Supplement by T. Northcote Toller (1995), 753, Enlarged Addenda and Corrigenda by Alistair Campbell to the Supplement by T. Northcote Toller (Oxford, Clarendon Press, 1995), 68. Føroysk-Donsk Orđabók av M.A.Jacobsen, Chr. Matras. 2 útgáva (Tórshavn, Føroya Fróđskaparfelag) (1961), 521; Føroysk-Donsk Orđabók av M. A. Jacobsen, Chr. Matras. Supplementsbind (1974), Die Gotische Bibel. Herausgegeben von W. Streitberg, Band 2, Gotisch-Griechisch-Deutsches Wörterbuch, 6 Auflage (Heidelberg, Universitätsverlag, C. Winter, 2000), 180. A Gothic Etymological Dictionary by Lehmann Winfred P. Based on the 3rd. edition of Vergleichendes Wörterbuch der gotischen Sprache by Sigmund Feist (Leiden, E. J. Brill, 1986), 712. Gotisches Wörterbuch von G. Köbler (Leiden, E. J. Brill, 1989), 716. An Icelandic-English Dictionary by Richard Gleasby, revised, enlarged and completed by Gudbrand Vigfusson. Second ed. with supplement by Sir William A.Craigie – Oxford: Clarendon Press, 2003.– 833. A Middle-English Dictionary Containing Words Used by English Writers From the Twelfth to the Thirteenth Century by F. H. Stratmann. A New Ed. Re-arranged, Revised, and Enlarged by H. Bradley (Oxford, Clarendon Press, 1967), 708. Mittelhochdeutsches Handwörterbuch von Matthias Lexer. Mit einer Einleitung von Kurt Gärtner. Bnd. I: Wortfamilien A –M. – 2262 S.; Bnd. II. Wortfamilien N – U. – 2050 S.; Bnd.III. Wortfamilien V/W – Z. – 1226 + 406. – Stuttgart: S.Hirzel, Wissenschaftliche Verlagsgesellschaft, 1992. Old Frisian Etymological Dictionary by D. Boutkan, S. Siebinga. Leiden Indo-European Etymological Dictionary Series 1 (Leiden; Boston, E. J. Brill, 2005), 598. Ordbog Til Det Ældre Danske Sprog (1300 – 1700) af Otto Kalkar i 6 Bind1: A – F + Tillæg og Rettelser, 838 + 65; Bnd. 2: G – L, 895; Bnd. 3: M – S, 908; Bnd. 4: S – Ø, 1018; Bnd. 5: A – Ø, 1222 (København, H. H. Theiles Bogtrykkeri, 1881– 1918); Bnd. 6: Kilder og Hjælpemidler. Efterskrift, 262 (København, Akademisk Forlag, 1976). Vergleichendes Wörterbuch der gotischen Sprache. Mit Einschluss des Krimgotischen und sonstiger zerstreuter Überreste des Gotischen von Sigmund Feist. Dritte neubearbeitete und vermehrte Auflage (Leiden,J. Brill, 1939), 710.